The Role of Perceived Ease of Use and Cashback Promotions on Impulsive Purchases of Shopeepay Users - Yoma, Melita Apri; Desiyanti, Rika (Politeknik STMI Jakarta, 2024)
The impact of development technology from product digital wallet against impulse buying is a significant phenomenon. This study aims to analyze the effect of perceived ease of use, cashback promotions, and financial literacy on impulse buyers of shopeepay users. Respondents used were Faculty of Business Economics students at private universities in Padang City. This research uses a purposive sampling technique with 80 respondents. The validity method was carried out using Confirmatory Factor Analysis (CFA), while multiple regression analysis using the STATA application was used to test the research hypothesis. The results showed that perceived ease of use and cashback promotions had a positive influence on impulse purchases, while financial literacy did not show a significant effect. The contribution of this research is to provide a deeper understanding of the factors that influence impulse buying in the digital era, especially those related to perceived ease of use, cashback promotions, and financial literacy in using shopeepay.